Environment, Green Technology, and Engineering International Conference 2018
DOI: 10.3390/proceedings2201280
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy Enhancement for Land Cover Classification Using LiDAR and Multitemporal Sentinel 2 Images in a Forested Watershed

Abstract: Mapping land cover with high accuracy has become a reality with the application of current remote sensing techniques. Due to the specific spectral response of the vegetation, soil and vegetation indices are adequate tools to help in the discrimination of land uses. Additionally, the accuracy of satellite imagery classification can be improved using multitemporal series combined with LiDAR data. This datafusion takes advantage of the information provided by LiDAR for the vegetation cover density, and the capabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 16 publications
0
9
0
2
Order By: Relevance
“…The studies on the implementation of Sentinel-2 in land cover/use monitoring have been reported in many countries across the world, including Europe, Asia, America, and Africa. Many studies that have been reported in developed countries, especially in Europe, integrated Sentinel-2 data with contemporary datasets such as LiDAR and UAVs datasets [86,117,138], while studies, based in developing countries, combined Sentinel-2 data with other open-source data such as Sentinel-1 SAR data and Landsat [139,140].…”
Section: Specific Applications Of Sentinel-2 In Land Cover/land Use Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies on the implementation of Sentinel-2 in land cover/use monitoring have been reported in many countries across the world, including Europe, Asia, America, and Africa. Many studies that have been reported in developed countries, especially in Europe, integrated Sentinel-2 data with contemporary datasets such as LiDAR and UAVs datasets [86,117,138], while studies, based in developing countries, combined Sentinel-2 data with other open-source data such as Sentinel-1 SAR data and Landsat [139,140].…”
Section: Specific Applications Of Sentinel-2 In Land Cover/land Use Monitoringmentioning
confidence: 99%
“…For example, Puliti, et al [146] reported the use of Sentinel-2 in forest inventories in Norway. The increasing combination of UAVs [146,147] and LiDAR [86,117] datasets with Sentinel-2 has shown promise and was highly accurate in describing different forest attributes.…”
Section: Sentinel-2 For Forest Monitoringmentioning
confidence: 99%
“…Among the vast array of kinds of remotely sensed data, multispectral optical images are still considered the most feasible and cost-effective option for monitoring extensive forest areas [14]. In recent years, multiple approaches for mapping forest dynamics have been developed using time series (TS) of multispectral optical satellite data that are freely available online such as in Landsat, MODIS, and, since 2015, Sentinel-2 data [14][15][16][17][18][19]. The analysis of changes in spectral signatures from TS of satellite images is well-documented as an efficient method for mapping temporal changes in forest environments [18,20].…”
Section: Introductionmentioning
confidence: 99%
“…The studies based on forest species classification involving Sentinel-2 images are still recent [23,33,[83][84][85][86]. The classification with S2 images of forest tree species in southwestern France obtained an overall accuracy above 90%, for plantations such as aspen (Populus tremula) and red oak (Quercus rubra).…”
Section: Maps Of Forest Lclu and Accuracy Assessmentmentioning
confidence: 99%